EFFECT OF DIAMETER BEARING MOUNTS TO STRESS CONCENTRATION FACTOR ON TRUCK GEARBOX CASING - Siregar, Rakhmad Arief; Siahaan, Muhammad Yusuf Rahmansyah; Rizal, Mahmud (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2024)
The present study examines the effect of diameter bearing mounts to the stress concentration factor. Three commercial truck gearbox casings were selected for redrawing using CATIA. The gearbox casing is then converted into a FEM model in ANSYS. It has a bore ratio (the ratio of the largest diameter to the smallest diameter of the bearing diameter) of 1.8, 1.5 and 1.4. By applying pressure to the upper gearbox casing for static and dynamic conditions, the total deformation response and equivalent stress are investigated. The deformations and equivalent stresses on the three models of gearbox were determined and discussed. It was found that the bore ratio of the gearbox showed significant differences in results on deformations and equivalent stress. Based on the equivalent stress data of view A, which is the side of the gearbox casing connected to the engine, the stress concentration factor results are consistent with the bore ratio.